Heavy metals detection with paper-based electrochemical sensors - Ding, Ruiyu (2021)
This feature article summarizes recent works in paper-based potentiometry and voltammetry in heavy metal determination. Interactions of paper substrates with heavy metals, influence on the sensing response, and modification methods applied to paper substrates to improve the performance of recently developed electrochemical sensors are discussed. Since the rekin-dling of interest in paper-based analytical devices, methodologies and electrode designs for heavy metal determinations are highlighted. Promising aspects of the use of these sensors for samples containing solids, and the increased versatility of the use of paper in analytics offers the possibility of increased acceptance of these low-cost platforms.